Physical Quality Of Edible Film From Duck Feet Gelatin Using Various Glycerol Concentrations - Gumilar, Jajang; Aulia Andiati, Hana; Wulandari, Eka (International Journal of Scientific Research and Management (IJSRM), 2024)
Edible film is a type of packaging that can be consumed, can coat food products, and can be decomposed naturally (biodegradable). This research aims to assess the effect of applying glycerol on the physical quality of edible film from duck's feet gelatin. This research used a completely randomized design (CRD) followed by the Tukey test. The treatment was the use of 10% (T1), 20% (T2), 30% (T3), 40% (T4), and 50% (T5) glycerol. The treatments were repeated three times. The findings indicated that the use of glycerol had a significant difference in the yield, thickness, tensile strength, and Young's modulus of edible film (P0.05). The optimal glycerol concentration for edible film in this study was obtained by using 10% glycerol.